2020
DOI: 10.1002/jmv.25855
|View full text |Cite
|
Sign up to set email alerts
|

False negative of RT‐PCR and prolonged nucleic acid conversion in COVID‐19: Rather than recurrence

Abstract: All procedures followed in this study were in accordance with the 1964 Helsinki Declaration and later versions. Oral consent was obtained from patients involved before enrollment when data were collected retrospectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
493
7
11

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 483 publications
(538 citation statements)
references
References 7 publications
16
493
7
11
Order By: Relevance
“…Some studies reported that potentially high false-negative rate of real-time reverse-transcriptase RT-PCR testing for SARS-CoV-2 and patients experienced a "turn positive" of nucleic acid detection by RT-PCR test for SARS-CoV-2 after two consecutive negative results. [19,30] For suspected cases, the nasopharyngeal swab should be taken, but waiting for the test results should not delay treatment. Serology tests for detecting the antibody can also be useful for COVID-19 diagnosis if available.…”
Section: Appropriate Laboratory Tests For Covid 19 Should Be Chosenmentioning
confidence: 99%
“…Some studies reported that potentially high false-negative rate of real-time reverse-transcriptase RT-PCR testing for SARS-CoV-2 and patients experienced a "turn positive" of nucleic acid detection by RT-PCR test for SARS-CoV-2 after two consecutive negative results. [19,30] For suspected cases, the nasopharyngeal swab should be taken, but waiting for the test results should not delay treatment. Serology tests for detecting the antibody can also be useful for COVID-19 diagnosis if available.…”
Section: Appropriate Laboratory Tests For Covid 19 Should Be Chosenmentioning
confidence: 99%
“…20 This study demonstrated a rate of re-detectable positive nucleic acid as high as 52.7% (39/74) despite strict adherence to domestic guidelines on discharge criteria, which may be attributed to the fact that SARS-CoV-2 mainly resides in the lower respiratory system. 21,22 In addition, possible deviation in specimen collection may lead to false negativity of nucleic testing and consequently inappropriate discharge decisions, 23,24 resulting in recurrence and even deterioration of the disease. The 20 patients with re-detectable positive nucleic acid displayed decline in lymphocyte subsets on the second admission, which was similar to the changes of initial infection.…”
Section: The Association Of Sars-cov-2 Antibodies With Re-detectablementioning
confidence: 99%
“…8 SARS-CoV-2 RNA has also been detected in throat or nasopharyngeal swabs more than 20 days after negative test results. 9 In another report among 18 patients, viral burdens (as determined by PCR cycle threshold) were generally lower than, and had declined substantially from, values during peak of illness. 10 At the time of postrecovery positive test results, the patients described in these reports had few, if any, symptoms, and when radiographically examined, they demonstrated stable or improving pneumonia.…”
mentioning
confidence: 93%